Haji Batin Sulaiman’s Thought in ʿAqīdah Education - Masrin, Suryan; Rusydi Sulaiman; Ahmad Fadholi (Scientia: Jurnal Hasil Penelitian, 2025)
This article examines the religious educational thought of Haji Batin Sulaiman, a local cleric whose intellectual influence developed on Bangka Island from the late nineteenth to the early twentieth century. Haji Batin Sulaiman placed strong emphasis on issues of tawḥīd within a society still shaped by local traditions and syncretic beliefs. His ideas are reflected not only through his oral daʿwah activities but also through several written works in Malay text using Arabic script, including a translation of the ḥadīth “man ʿarafa nafsahu faqad ʿarafa rabbahu”, the Five Articles of Faith, and Sair Tsani, which serves as the concluding section of Asrār al-Insān by Shaykh Nūr al-Dīn al-Rānīrī.This study aims to identify and map Haji Batin Sulaiman’s perspectives on ʿaqīdah education as presented in his writings, and to explore their contribution to the development of Islamic education on Bangka Island. Employing a literature-based research design with historical and content-analysis approaches, this study involves data collection through source criticism, transliteration, interpretation, and textual analysis.The findings reveal that Haji Batin Sulaiman’s conceptualization of ʿaqīdah education centers on strengthening monotheism through an integrated rational, spiritual, and Sufi-oriented approach. Analysis of the manuscripts indicates four key emphases: (1) strengthening tawḥīd through self-knowledge, (2) reinforcing faith through the Five Creeds, (3) internalizing faith through oral and written traditions, and (4) implementing ʿaqīdah education through rational and textual methods. Overall, Haji Batin Sulaiman’s thought represents an important intellectual legacy and provides valuable insight for developing contextual Islamic education rooted in the principles of tawḥīd.